2014
DOI: 10.1590/s1806-83242013005000030
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic tumors: a 14-year retrospective study in Santa Catarina, Brazil

Abstract: Odontogenic tumors (OTs) are lesions that develop exclusively on maxillary bones, and form a heterogeneous group. They vary from hamartomatous lesions to benign and malign tumors. Although they are rarely observed in dentistry clinics, it is extremely important for the dentist to be aware of them. The aim of this study was to investigate the incidence of odontogenic tumors diagnosed in the population of Florianópo-lis, Santa Catarina, Brazil. Cases of odontogenic tumors were selected from the anatomopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 19 publications
6
13
0
6
Order By: Relevance
“…Corroborating with other studies (12,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), in our sample, benign tumors were prevalent. This low frequency of malignant tumors is similar to those reported in others countries (7)(8)(9)(10)(11)(12)19), but it is different than those reported in China that present more than 5% of cases as malignant tumors (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Corroborating with other studies (12,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), in our sample, benign tumors were prevalent. This low frequency of malignant tumors is similar to those reported in others countries (7)(8)(9)(10)(11)(12)19), but it is different than those reported in China that present more than 5% of cases as malignant tumors (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 91%
“…This low frequency of malignant tumors is similar to those reported in others countries (7)(8)(9)(10)(11)(12)19), but it is different than those reported in China that present more than 5% of cases as malignant tumors (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). We have observed a greater incidence of OTs in the female gender, result also found by Gaitán-Cepeda et al (30).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These features were similar to the previously published literature. 19 Females are commonly affected than males, with the male to female ratio of 1:1.2, and these findings were not in accordance to the epidemiological reports of Ramos Gde O et al, 20 which have reported male predominance. Association of KCOT with nevoid basal cell carcinoma syndrome was recorded to be 6% in the previous literature, and interestingly, studies conducted in Brazil showed frequency as high as 40%.…”
Section: Keratocystic Odontogenic Tumormentioning
confidence: 77%